Analysis of factor affecting Islamic commercial bank financing for the agricultural sector in Indonesia - Satrio Arif Wicaksono; Yeny Fitriyani (Asian Journal of Islamic Management (AJIM), 2020)
Purpose: This study aims to analyse the factors that influence Islamic commercial bank financing for the agricultural sector in Indonesia from January 2015 to April 2019.Methodology: Variables used in this study are Agricultural Financing, DPK, NPF, Inflation, Exchange Rates, SBIS, and IPI. The method used in this research is the VAR/VECM method with Impulse Response Function (IRF) analysis and Forecast Error Variance Decomposition (FEVD).Findings: The results show that the variables that significantly influence agricultural financing in the long-term are DPK, Exchange Rate, and IPI. Taking a closer detail, IPI variable has a positive effect, while the DPK and Exchange Rate have a negative effect on agricultural financing. Then NPF, inflation, and SBIS have no effect on agricultural financing in the short and long-term. Based on the results of FEVD, the variable that has the greatest contribution to agricultural financing is DPK compared to Exchange Rate and IPI.Practical applications: Islamic bank directors prioritize efforts to increase funding in order to encourage an increase in the portion of financing in the agricultural sector.Originality: This study examines the effect of financial and macroeconomic performance on mudharabah financing in the short and long term in Indonesia.